IMPLEMENTASI MATA KULIAH PENDIDIKAN MULTIKULTURAL DI IAI AGUS SALIM METRO LAMPUNG - M. Fuad Asyari (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
The background in this study is to be able to instill multicultural values that exist in Indonesia, especially in Lampung Province, with many differences in ethnicity, a religion, culture, race, ethnicity and so on. To protect it from the many conflicts, IAI Agus Salim Metro Lampung university carries the slogan Multicultural Campus and includes the concept in the multicultural education course. This study aims to how iai Agus Salim Metro Lampung students' perceptions of the implementation of multicultural education courses, in terms oflecture concepts, and learning strategies. The type of research used is of the qualitative research type, through a descriptive model. Data collection techniques with field studies are through interviews. Primary data was obtained from semester students of the department at IAI Agus Salim Metro Lampung, while secondary data was obtained from scientific journals and books. Based on the results of the research obtained, multiculturalism as harmonization between each other, and mutual understanding. The implementation of the eyes of the soup is that students do not discriminate, lecturers are fair, there is deliberation. Institutional Support in the form of cooperation, gender sensitivity, student organization orientation, harmonious relations between lecturers and employees.